Quality of Life in Cancer Patients and its Related Factors - Abdollahzadeh, Farahnaz (Tabriz University of Medical Sciences, 2012)
Introduction: Despite the importance of quality of life (QOL) in outcomes of cancer pa-tients, there have been a few Iranian studies investigating the Iranian patients’ quality of life. The present study aimed to assess the cancer patients’ QOL and its related factors. Methods: This cross-sectional study conducted in Shahid Ghazi Tabatabaei Hospital affiliated to Tabriz University of Medical Sciences in 2009. The samples included 150 cancer patients aged more than 18 years who were aware of their own diagnosis. They were selected through convenient sampling method and European Organization for Research and Treatment of Cancer–Quality of life questionnaire (EORTC–QOL 30) were completed. Results: Our findings showed that 44.1% of the patients had moderate QOL. QOL had a significant correlation with the level of family support (p = 0.002). Conclusion: Many of cancer patients have a moderate QOL. However, confirmation of such finding requires further investigations.